Two new species and a new synonym of Oedignatha Thorell, 1881 from China (Araneae: Liocranidae) - Zhang, Haibin; Mu, Yannan; Zhang, Feng (Zootaxa, 2025)
Two new species of Oedignatha Thorell, 1881 are described from China: O. tongbiguan sp. nov. (♂♀) from Yunnan Province and O. zham sp. nov. (♂♀) from Xizang Autonomous Region. Images and detailed descriptions of the habitus and copulatory organs of both species are provided. Moreover, Koppe ninger Chu & Li, 2023 is proposed as a junior synonym of Oedignatha dian Lu & Li, 2023.